Mullite whiskers grown from erbia-doped aluminum hydroxide-silica gel - de Souza, M. F.; Yamamoto, J.; Regiani, I; Paiva-Santos, C. O.; de Souza, DPF (Amer Ceramic Soc, 2000)
Mullite whiskers and anisotropic grains that were derived from erbia-doped aluminum hydroxide-silica gel were studied. Firing 3.0-mol%-erbia-doped isostatically pressed pellets at 1600 degrees C for 1.0-8.0 h resulted in a high surface concentration of mullite whiskers. Their c-axes were aligned preferentially along the pellet surface; the maximum length was 50 mu m, and the maximum aspect ratio was 23. The pellet surface was fully covered by mullite whiskers, and small anisotropic grains with a low aspect ratio were observed in the bulk. The voids that were observed in the fracture surfaces were covered fully by mullite whiskers. The large number of voids resulted in an apparent density of 1.60 g/cm(3) in the sintered pellets. The molar ratio of alumina to silica in the whiskers was in the range of 1.30-1.45 tan average value of 1.31), regardless of whether the alumina/silica powder compositions were mixed in a 3:2 or 2:1 ratio.